Érdekek egybeesése és ütközése: Szemelvények a MOL államhoz fűződő kapcsolataiból - Péter Vince (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
– MOL Plc as a national champion does not simply take part in the implementation of the state's decisions but the company's cooperation is needed in realizing the economic, political and social considerations of the authorities. Therefore the company is provided with special preferential treatment. Besides, MOL can take advantage of its efficient bargaining power to secure the authorities' favorable decisions in important cases. The regulations and special decisions of the European Union limit MOL's position as a national champion. In cases belonging exclusively to national competence the main position of authorities was to prevent the emergence of foreign ownership control. In other cases, the authorities behaved differently: sometimes they contributed to the consolidation of the company's position as national champion, sometimes they weakened it with their decisions. The relationship of the company and the state is thus characterized not only by matching but conflicting interests too.
Keywords: D21; D23; L1; L2; L5; 330; national champion; corporate management; relationship and interactions of the company and the state; changes of ownership structure; Unternehmenserfolg; Management; Eigentümerstruktur; Staatliche Einflussnahme; Ungarn